Improved biomechanics in experimental chronic rotator cuff repair after shockwaves is not reflected by bone microarchitecture. - Xaver Feichtinger; Patrick Heimel; Stefan Tangl; Claudia Keibl; Sylvia Nürnberger; Jakob Emanuel Schanda; David Hercher; Roland Kocijan; Heinz Redl; Johannes Grillari; Christian Fialka; Rainer Mittermayr (PLoS ONE)
Purpose The aim of this study was to investigate the effect of extracorporeal shockwave therapy (ESWT) on bone microstructure as well as the bone-tendon-interface and the musculo-tendinous transition zone to explain the previously shown improved biomechanics in a degenerative rotator cuff tear animal model. This study hypothesized that biomechanical improvements related to ESWT are a result of improved bone microstructure and muscle tendon properties. Methods In this controlled laboratory study unilateral supraspinatus (SSP) tendon detachment was performed in 48 male Sprague-Dawley rats. After a degeneration period of three weeks, SSP tendon was reconstructed transosseously. Rats were randomly assigned into three groups (n = 16 per group): control (noSW); intraoperative shockwave treatment (IntraSW); intra- and postoperative shockwave treatment (IntraPostSW). Eight weeks after SSP repair, all rats were sacrificed and underwent bone microstructure analysis as well as histological and immunohistochemical analyses. Results With exception of cortical porosity at the tendon area, bone microstructure analyses revealed no significant differences between the three study groups regarding cortical and trabecular bone parameters. Cortical Porosity at the Tendon Area was lowest in the IntraPostSW (p≤0.05) group. Histological analyses showed well-regenerated muscle and tendon structures in all groups. Immunohistochemistry detected augmented angiogenesis at the musculo-tendinous transition zone in both shockwave groups indicated by CD31 positive stained blood vessels. Conclusion In conclusion, bone microarchitecture changes are not responsible for previously described improved biomechanical results after shockwave treatment in rotator cuff repair in rodents. Immunohistochemical analysis showed neovascularization at the musculo-tendinous transition zone within ESWT-treated animals. Further studies focusing on neovascularization at the musculo-tendinous transition zone are necessary to explain the enhanced biomechanical and functional properties observed previously. Clinical relevance In patients treated with a double-row SSP tendon repair, an improvement in healing through ESWT, especially in this area, could prevent a failure of the medial row, which is considered a constantly observed tear pattern.